Correlation between Game-Based Learning Application and Students’ Writing Skills: A Study at a State High School in Serang - Ratih Ayu Wulandari; Asep Muhyidin; Syafrizal (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
As one of the four language skills, writing is considered difficult since it requires the mastery of all other skills. Many students often face difficulties in learning writing, including narrative. To handle this situation, English teachers need to apply innovative teaching methods, such as game-based learning. This study was conducted to investigate the correlation between game-based learning application using Wordwall and students’ writing skills at senior high school level. A quantitative study with correlational design employed where students filled questionnaires on game-based learning application and narrative writing test. Thirty-eight eleventh-graders from a public senior high school in Serang, Banten Province, participated in the study. The data collected were analyzed using Pearson-Product Moment Correlation Test through the SPSS version 27. The results showed that the r-count 0.722 > r-table 0.320 with the Sig. (2-tailed) 0.000 < 0.05, indicated a strong positive correlation between game-based learning application and students’ writing skills. It also revealed that game-based learning application contributed for 52.1% to the students’ writing skills, while the rest were influenced by other factors which were not examined in this study. These results suggested that game-based learning application could serve as one of the potential alternative methods to enhance students’ learning outcomes.